REPRESENTASI SENSUALITAS PEREMPUAN DALAM IKLAN ZILINGO (STUDI SEMIOTIKA DENGAN CHARLES SANDERS PIERCE) - Hanifah, Ummy (INTERPRETASI : Communication & Public Relation, 2024)
Between mass media and women likened two sides of coin that can’t be separated. Advertising describes women as a weak creature. The role of women that always describe in ads always describing domestic roles. Women also exploited by sensuality that they have like their body as a mean of attracting in mass media industry. This research is researching Zilingo version Classy or Glossy. the representation of women on this ad represented in the form dancing women, flirting with ex her boyfriend, by being exploited with their body. The technique that used ini ad by using jingle or interesting slogans. The research wants to know how Zilingo represented women’s sensuality by selecting sign like picture or other signs. The approach used in this research is semiotic theory from Charles Sanders Pierce known as a theory triangle meaning in analyzing the sign. The object of this research consisting of word, picture in Zilingo ad. The result shows sensual women, according to Zilingo, describe having slim stature, black hair, beautiful face and break the traditional style of women. Beside that, Zilingo ad also have a message as a picture frame and social frame. In a picture frame, women try to attract alluring. And in social image, women being active againstthe traditional concept of women. Of course, it is suitable with the main purpose of ad is to persuade consument in order to use their product, service in a form of creative advertising strategy.